Wybrane zagadnienia oceny ośrodków odpowiedzialności za zyski na przykładzie przedsiębiorstwa handlowego - Ossowski, Marek (The Selected Problems of Rating Profit Centers in the Commerce Company., 2006)
The following article is devoted to profit centers in the commerce company. In the first part, the author presents theoretical basis connected with the decentralization of management, explains definitions and types of responsibility centers found in literature. The second part concerns the system of marking the tradesmen's work in the commerce company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 62-70